PENGEMBANGAN MULTIMEDIA SMART LEARNING BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEPTUAL SISWA KELAS VII PADA MATERI PENCEMARAN LINGKUNGAN - Satria Buana; Muhammad Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the gap in the availability of learning media specifically designed to support the discovery stage in environmental pollution, despite the increasing integration of technology in education. This study aims to develop a valid, practical, and effective Discovery Learning-based Smart Learning multimedia to improve seventh-grade students' conceptual understanding of environmental pollution. The method used was Research and Development with the ADDIE development model, which includes the stages of Analyze, Design, Develop, Implement, and Evaluate. The research subjects included content experts, media experts, instructional design experts, science teachers, and seventh-grade students to test the product's feasibility. The results showed that the instrument's interactivity met academic and technical feasibility criteria. The design evaluation showed a "High" category for various indicators, such as readability, color compatibility, and navigation button recognition, which achieved the highest score. Comprehensively, the developed multimedia was declared highly suitable for use as a medium for reinforcing concepts in the learning process at school.